HUBUNGAN PENGETAHUAN DAN PERSONAL HYGIENE DENGAN RISIKO KEJADIAN SKABIES PADA SANTRI LAKI-LAKI DI PESANTREN MARKAZ AL-ISHLAH AL-AZIZIYAH BANDA ACEH - Sri Rosita; Rahmayani Rahmayani; Evi Dewi Yani; Yunita Yunita; Tika Indiraswari; M. Rio Prayudiski (Universitas Ubudiyah Indonesia, 2025)
Background of the Problem: The quality of health services is one of the main indicators used to assess the performance of health facilities. Patient satisfaction reflects the extent to which healthcare institutions can meet community expectations and needs through the services provided. This study aims to determine the relationship between service quality and patient satisfaction at Darul Imarah Public Health Center, Aceh Besar District. This research employed a quantitative approach with a cross-sectional design. The study population consisted of all patients visiting Darul Imarah Health Center, totaling 2,024 individuals, with a sample of 96 respondents selected using an accidental sampling technique. Data were collected through interviews using a structured questionnaire and analyzed using the Chi-Square test with a 95% confidence level (? = 0.05). The results showed that the majority of patients (65.6%) were satisfied with the healthcare services provided. Most respondents rated the quality of services in the dimensions of reliability (59.4%), responsiveness (59.4%), assurance (68.8%), empathy (62.5%), and tangibles (62.5%) as good. Statistical analysis revealed a significant relationship between all dimensions of service quality and patient satisfaction (p < 0.05). In conclusion, good service quality in the aspects of reliability, responsiveness, assurance, empathy, and tangibles influences patient satisfaction. It is recommended that the health center continuously improve service quality, particularly in responsiveness and empathy, to enhance overall patient satisfaction. Keywords: Service Quality, Patient Satisfaction, Darul Imarah